Cytoplasmic and nuclear NFATc3 cooperatively contributes to vascular smooth muscle cell dysfunction and drives aortic aneurysm and dissection - Xiu Liu; Li Zhao; Deshen Liu; Lingna Zhao; Yonghua Tuo; Qinbao Peng; Fangze Huang; Zhengkun Song; Chuanjie Niu; Xiaoxia He; Yu Xu; Jun Wan; et al. (Acta Pharmaceutica Sinica B)
This study investigated the role of the nuclear factor of activated T cells c3 (NFATc3) in vascular smooth muscle cells (VSMCs) during aortic aneurysm and dissection (AAD) progression and the underlying molecular mechanisms. Cytoplasmic and nuclear NFATc3 levels were elevated in human and mouse AAD. VSMC–NFATc3 deletion reduced thoracic AAD (TAAD) and abdominal aortic aneurysm (AAA) progression in mice, contrary to VSMC–NFATc3 overexpression. VSMC–NFATc3 deletion reduced extracellular matrix (ECM) degradation and maintained the VSMC contractile phenotype. Nuclear NFATc3 targeted and transcriptionally upregulated matrix metalloproteinase 9 (MMP9) and MMP2, promoting ECM degradation and AAD development. NFATc3 promoted VSMC phenotypic switching by binding to eukaryotic elongation factor 2 (eEF2) and inhibiting its phosphorylation in the VSMC cytoplasm. Restoring eEF2 reversed the beneficial effects in VSMC-specific NFATc3-knockout mice. Cabamiquine—targets eEF2 and inhibits protein synthesis—inhibited AAD development and progression in VSMC-NFATc3-overexpressing mice. VSMC–NFATc3 promoted VSMC switch and ECM degradation while exacerbating AAD development, making it a novel potential therapeutic target for preventing and treating AAD.